2010
DOI: 10.1016/j.jtcvs.2009.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral and somatic oxygen saturation decrease after delayed sternal closure in children after cardiac surgery

Abstract: Cerebral and somatic regional oxygen saturation decrease after delayed sternal closure in children recovering from congenital cardiac surgery. These indices are in agreement with other physiologic indicators of cardiac performance, suggesting mild and transient hemodynamic compromise after sternal closure. Cerebral and somatic regional oxygen saturation monitoring might be a useful adjunct during delayed sternal closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
(28 reference statements)
1
13
2
Order By: Relevance
“…With respect to changes in key physiologic parameters over time, we found that although mean heart rate and left atrial pressures were unchanged, mean blood pressure increased and inotrope score decreased in 12 hours after sternal closure which was in contradiction with Tabbutt and Horvath’s studies suggesting decrease in hemodynamic performance after sternal closure [8,22]. …”
Section: Discussioncontrasting
confidence: 62%
“…With respect to changes in key physiologic parameters over time, we found that although mean heart rate and left atrial pressures were unchanged, mean blood pressure increased and inotrope score decreased in 12 hours after sternal closure which was in contradiction with Tabbutt and Horvath’s studies suggesting decrease in hemodynamic performance after sternal closure [8,22]. …”
Section: Discussioncontrasting
confidence: 62%
“…Inotropic score was first described in the Boston Circulatory Arrest Study to quantify the amount of pharmacologic cardiovascular support required during the postoperative period [25]. Inotropic score has been used in other clinical studies as a measurement of illness severity [2, 3, 11, 15]. However, until recently, inotropic score has not been validated as a surrogate marker of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Significant changes in cardiorespiratory variables may occur during DSC . Cerebral and somatic regional oxygen saturations may decrease after DSC . With our technique, we managed pseudo‐sternal closure in stages.…”
Section: Discussionmentioning
confidence: 99%
“…1 Cerebral and somatic regional oxygen saturations may decrease after DSC. 2 With our technique, we managed pseudo-sternal closure in stages. Therefore, when we performed ''true-sternal closure,'' the sternum had already been closed under the Esmarch, and the influence of chest closure was minimized.…”
Section: Discussionmentioning
confidence: 99%